Differential Expression of Three α-Galactosidase Genes and a Single β-Galactosidase Gene from Aspergillus niger - de Vries, Ronald P. (American Society for Microbiology, 1999)
A gene encoding a third α-galactosidase (AglB) from Aspergillus niger has been cloned and sequenced. The gene consists of an open reading frame of 1,750 bp containing six introns. The gene encodes a protein of 443 amino acids which contains a eukaryotic signal sequence of 16 amino acids and seven putative N-glycosylation sites. The mature protein has a calculated molecular mass of 48,835 Da and a predicted pI of 4.6. An alignment of the AglB amino acid sequence with those of other α-galactosidases revealed that it belongs to a subfamily of α-galactosidases that also includes A. niger AglA. A. niger AglC belongs to a different subfamily that consists mainly of prokaryotic α-galactosidases. The expression of aglA, aglB, aglC, and lacA, the latter of which encodes an A. niger β-galactosidase, has been studied by using a number of monomeric, oligomeric, and polymeric compounds as growth substrates. Expression of aglA is only detected on galactose and galactose-containing oligomers and polymers. The aglB gene is expressed on all of the carbon sources tested, including glucose. Elevated expression was observed on xylan, which could be assigned to regulation via XlnR, the xylanolytic transcriptional activator. Expression of aglC was only observed on glucose, fructose, and combinations of glucose with xylose and galactose. High expression of lacA was detected on arabinose, xylose, xylan, and pectin. Similar to aglB, the expression on xylose and xylan can be assigned to regulation via XlnR. All four genes have distinct expression patterns which seem to mirror the natural substrates of the encoded proteins.